COMPARISON ANALYSIS OF FINANCIAL FREEDOM OF THE REPUBLIC OF KAZAKHSTAN WITH THE ISLAMIC REPUBLIC OF IRAN - Amir Mohammad Sohrabian; Mohammad Amin Sohrabian (European Scientific Journal, ESJ, 2014)
In this article we will focus on the financial freedom of Kazakhstan versus Iran, emphasizing the proper reformation and implementation on ongoing reforms of financial and economical activities in Kazakhstan which makes Kazakhstan to be one of the 20 largest score improvements in the 2012 Index and an evidence for other capable Asian countries such as Iran with seriously degraded economic dynamism as a result of it’s political instability. Comparison analysis of the current data of Financail Freedom published by reputed organization with the country’s current financial climate.